Reduced islet function contributes to impaired glucose homeostasis in fructose-fed mice - Asghar, Zeenat A. (Am J Physiol Endocrinol Metab, 2017)
Increased sugar consumption, particularly fructose, in the form of sweetened beverages and sweeteners in our diet adversely affects metabolic health. Because these effects are associated with features of the metabolic syndrome in humans, the direct effect of fructose on pancreatic islet function is unknown. Therefore, we examined the islet phenotype of mice fed excess fructose. Fructose-fed mice exhibited fasting hyperglycemia and glucose intolerance but not hyperinsulinemia, dyslipidemia, or hyperuricemia. Islet function was impaired, with decreased glucose-stimulated insulin secretion and increased glucagon secretion and high fructose consumption leading to α-cell proliferation and upregulation of the fructose transporter GLUT5, which was localized only in α-cells. Our studies demonstrate that excess fructose consumption contributes to hyperglycemia by affecting both β- and α-cells of islets in mice.